2008
DOI: 10.1051/apido:2008053
|View full text |Cite
|
Sign up to set email alerts
|

Floral scents experienced within the colony affect long-term foraging preferences in honeybees

Abstract: To cite this version:Andrés Arenas, Vanesa M. Fernández, Walter M. Farina. Floral scents experienced within the colony affect long-term foraging preferences in honeybees. Apidologie, Springer Verlag, 2008, 39 (6) Abstract -Food scents circulating inside beehives influence foraging preferences in the field. However, the persistence and nature of the prior experience that lead to this biased response remain unknown. To determine how long honeybees show a food preference after experiencing a scented food inside t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…Colony H2 (2009, ~2000 adult individuals) was kept in a one-frame observation hive. The observation hives were set up in a flight chamber (6ϫ3ϫ2m 3 ) (see Arenas et al, 2008), which prevented potential interference from other bee colonies during the recordings. One lateral side of the flight chamber remained open so that foraging in the surrounding environment was not restricted.…”
Section: Study Site and Beesmentioning
confidence: 99%
“…Colony H2 (2009, ~2000 adult individuals) was kept in a one-frame observation hive. The observation hives were set up in a flight chamber (6ϫ3ϫ2m 3 ) (see Arenas et al, 2008), which prevented potential interference from other bee colonies during the recordings. One lateral side of the flight chamber remained open so that foraging in the surrounding environment was not restricted.…”
Section: Study Site and Beesmentioning
confidence: 99%
“…In nectar feeders, olfactory information about the food sources is propagated during the distribution of the nectar within the colony (in honey bees: Pankiw et al, 2004;Grüter et al, 2006;in Camponotus ants: Provecho and Josens, 2009). In honey bees, social sharing of scented food allows other foragers and even workers not directly involved in foraging tasks to obtain information from individuals that actively participate in resource exploitation (Arenas et al, 2007(Arenas et al, , 2008. Here, we demonstrated that odours of host plants learned through the waste can also be used by foragers when making decisions outside of the nest.…”
Section: Discussionmentioning
confidence: 70%
“…However, in the social environment of the hive, bees learn odors from each other, e.g., by trophallactic transfer of scented nectar (Arenas et al 2008;Farina et al 2005Farina et al , 2007Gil and De Marco 2005) and during dance communication (Grüter and Farina 2009). Hence, reduction in learning found in our study might be a specific effect of colony odor on the learning of sting pheromone odor IAA.…”
Section: Discussionmentioning
confidence: 99%